Peningkatan Kemampuan Membuat Media Pembelajaran Bahasa Arab Menggunakan Aplikasi “Camtasia Studio” pada Mahasiswa Program Studi Pendidikan Bahasa Arab UIN Sunan Ampel Surabaya - Ahmad Fauzi (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2019)
With the existence of learning media, not only overcoming limitations possessed by teacher in teaching and learning process, but with the existence of learning media created direct interaction between teaching materials and students, that will facilitate students in learning. Therefore, researchers used the camtasia video media as one of the learning media for Arabic that will be developed by students of Sunan Ampel Surabaya State Islamic University in third semester. This study uses the Class Action Research method so that researchers get the maximum value from the media developed by students by using three times of practicum for media improvement. The purpose of this study is to develop technology-based Arabic language learning media, especially multimedia software that is already very familiar with students